Impact of inhalation injury on outcomes in critically ill burns patients: 12-year experience at a regional burns centre. Issue 6 (September 2022) - Charles, Walton N.; Collins, Declan; Mandalia, Sundhiya; Matwala, Kabir; Dutt, Atul; Tatlock, Jason; Singh, Suveer
Highlights: Severe inhalation injury is a significant risk factor for mortality. Facial burns, higher TBSA and older age also portended worse prognosis. However, the effect of mild inhalation injury was not significant. Registry-based studies are needed to further evaluate bronchoscopic grading. Abstract: Introduction: Burns inhalation injury increases the attributable mortality of burns related trauma. However, diagnostic uncertainties around bronchoscopically graded severity, and its effect on outcomes, remain. This study evaluated the impact of different bronchoscopic burns inhalation injury grades on outcomes. Methods: A single-centre cohort study of all patients admitted to the London Burns centre intensive care unit (BICU) over 12 years. Demographic data, burn and burns inhalation injury characteristics, and ICU-related parameters were collected retrospectively. The primary outcome was mortality. Secondary outcomes were hospital and ICU lengths of stay. The impact of pneumonia was determined. Univariate and multivariable Cox's proportional hazards regression analyses informed factors predicting mortality. Results: Burns inhalation injury was diagnosed in 84 of 231 (36%) critically ill burns patients; 20 mild (grade 1), 41 severe (grades 2/3) and 23 unclassified bronchoscopically. Median (IQR) total body surface area burned (TBSA) was 20% (10−40). Mortality was significantly higher in patients with burns inhalation injury vs those without burns inhalation injury (38/84 [45%] vs 35/147 [24%], p < 0.001). Patients with pneumonia had a higher mortality than those without (34/125 [27%] vs 8/71 [11%], p = 0.009). In multivariable analysis, severe burns inhalation injury significantly increased mortality (adjusted HR=2.14, 95%CI: 1.12–4.09, p = 0.022), compared with mild injury (adjusted HR=0.58, 95% CI: 0.18–1.86, p = 0.363). Facial burns (adjusted HR=3.13, 95%CI: 1.69–5.79, p < 0.001), higher TBSA (adjusted HR=1.05, 95%CI: 1.04–1.06, p < 0.001) and older age (adjusted HR=1.04, 95%CI: 1.02–1.07, p < 0.001) also independently predicted mortality, though pneumonia did not. Conclusions: Severe burns inhalation injury is a significant risk factor for mortality in critically ill burns patients. However, pneumonia did not increase mortality from burns inhalation injury. This work confirms prior implications of bronchoscopically graded burns inhalation injury. Further study is suggested, through registries, into the diagnostic accuracy and reliability of bronchoscopy in burns related lung injury.